Pengaruh Rhizobakteria Pelarut Fosfat Terhadap Pertumbuhan dan Ketahanan Tanaman Kedelai (Glycine max (L) Merill) terhadap Patogen Virus Mosaic - MAHADIPTHA, PUTU; SUDANA, I MADE; RAKA, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.2, April 2017, 2017)
The impact of solvent rhizobacteria phosphate on the growth and resistence of soybean (Glycine max (L.) Merill) towards mosaic virus phatogen This study aims to obtain isolates rizobakteri are able to increase the growth and survival of soybean plants. The design used was a randomized block design (RAK) with 14 treatments and 3 replications. The treatment consisted of 13 isolates of rhizobacteria and one as a control (no isolates rhizobakteria). This research is a pot with plant growth and survival variables include; plant height, number of branches, number of leaves, chlorophyll content, number of pods, number of seeds and seed weight, and predict the yield per hectare, phenol, salicylic acid and peroxidase. The results showed three isolates rizobakteri, which isolates Rf 53, Rf 6 and Rf 26 has a better ability than the other rhisobakteria isolates. The third isolates capable of increased plant height, number of branches, number of leaves, chlorophyll, number of pods, number of seeds and seed weight, and predict the yield per hectare. Events systemic acquired resistance (SAR) in plants, namely the accumulation of phenolic compounds, salicylic acid, peroxide, and jasmonik acid. Jasmonic acids able to produces related-proteins (PR-proteins) which is really functional for plants resistance towards pests or diseases.